Palmitic Acid Induces Production of Proinflammatory Cytokines Interleukin-6, Interleukin-1β, and Tumor Necrosis Factor-α via a NF-κB-Dependent Mechanism in HaCaT Keratinocytes - Bing-rong Zhou; Jia-an Zhang; Qian Zhang; Felicia Permatasari; Yang Xu; Di Wu; Zhi-qiang Yin; Dan Luo (Mediators of Inflammation)
To investigate whether palmitic acid can be responsible for the induction of inflammatory processes, HaCaT keratinocytes were treated with palmitic acid at pathophysiologically relevant concentrations. Secretion levels of interleukin-6 (IL-6), tumor necrosis factor-α (TNF-α), interleukin-1β (IL-1β), NF-κB nuclear translocation, NF-κB activation, Stat3 phosphorylation, and peroxisome proliferator-activated receptor alpha (PPARα) mRNA and protein levels, as well as the cell proliferation ability were measured at the end of the treatment and after 24 hours of recovery. Pyrrolidine dithiocarbamate (PDTC, a selective chemical inhibitor of NF-κB) and goat anti-human IL-6 polyclonal neutralizing antibody were used to inhibit NF-κB activation and IL-6 production, respectively. Our results showed that palmitic acid induced an upregulation of IL-6, TNF-α, IL-1β secretions, accompanied by NF-κB nuclear translocation and activation. Moreover, the effect of palmitic acid was accompanied by PPARα activation and Stat3 phosphorylation. Palmitic acid-induced IL-6, TNF-α, IL-1β productions were attenuated by NF-κB inhibitor PDTC. Palmitic acid was administered in amounts able to elicit significant hyperproliferation and can be attenuated by IL-6 blockage. These data demonstrate for the first time that palmitic acid can stimulate IL-6, TNF-α, IL-1β productions in HaCaT keratinocytes and cell proliferation, thereby potentially contributing to acne inflammation and pilosebaceous duct hyperkeratinization.